International trade and retailing - Carsten Eckel (Center for Economic Studies and ifo Institute (CESifo), 2009)
The New Trade Theory predicts that international trade lowers prices for consumers and expands the choices available to them. This study shows that both predictions may no longer hold once adjustments in the retail sector are taken into account. I present a new model of retailing in general equilibrium and explore its implications for a number of different shocks. The results demonstrate that retail assortments may remain constant if consumers have a low preference for diversity, and that consumer prices can even rise if the retail density is sufficiently low.
Keywords: F12; L11; L81; 330; International trade; retailing; diversity; market structure; welfare; monopolistic competition; Einzelhandelspreispolitik; Einzelhandel; Marktstruktur; Diversifikation; Neue Außenhandelstheorie; Internationaler Wettbewerb; Monopolistischer Wettbewerb; Wohlfahrtseffekt; Theorie